POTENSI DESA WISATA BUKIT BATU SEBAGAI DAYA TARIK WISATA DI KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Zahrona, Elma; Sumiarsih, Eni; Yanti, Risna (Puslitabmas Batam Tourism Polytecnic, 2025)
Research has been carried out in January – June 2024. This study aims to find out the potential of Bukit Batu Tourism Village as a tourist attraction in Bukit Batu District, Bengkalis Regency, to find out the development of Bukit Batu Tourism Village and the category of Bukit Batu Village based on the criteria for the development of tourist villages, and to find out the perception of tourists towards Bukit Batu Tourism Village. This study uses a qualitative descriptive analysis method, namely descriptive or explanatory research using tables. Data sources obtained from observations, literature studies, documentation and the dissemination of questionnaires or questionnaires. Then it was analyzed using Likert scale analysis. The results of the study show that the potential of Tourism Bukit Batu Tourism Village is the presence of nature, history and culture, accommodation, and culinary diversity. The results of the research on the development of Bukit Batu Tourism Village and the category of Bukit Batu Village based on the criteria for the development of tourist villages are that Bukit Batu Tourism Village is in the position of a developing village. Based on the results of tourists' perception of the potential of Bukit Batu Tourism Village by obtaining an overall average of 3.16 which is included in the good category, therefore the potential of Bukit Batu Tourism Village is worthy as a tourist attraction.